2013
DOI: 10.1186/1472-6920-13-171
|View full text |Cite
|
Sign up to set email alerts
|

Impact of personal goals on the internal medicine R4 subspecialty match: a Q methodology study

Abstract: BackgroundThere has been a decline in interest in general internal medicine that has resulted in a discrepancy between internal medicine residents’ choice in the R4 subspecialty match and societal need. Few studies have focused on the relative importance of personal goals and their impact on residents’ choice. The purpose of this study was to assess if internal medicine residents can be grouped based on their personal goals and how each group prioritizes these goals compared to each other. A secondary objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The greatest benefit of the Q methodology is that it forces a quasinormal distribution, so participants cannot choose the same response for every item (Daniels and Kassam, 2013). Study participants are asked to rank the order of the Q samples by using a grid referred to as the Q sort table.…”
Section: Q Sortingmentioning
confidence: 99%
“…The greatest benefit of the Q methodology is that it forces a quasinormal distribution, so participants cannot choose the same response for every item (Daniels and Kassam, 2013). Study participants are asked to rank the order of the Q samples by using a grid referred to as the Q sort table.…”
Section: Q Sortingmentioning
confidence: 99%
“…A systematic evaluation of how these factors may affect recruitment into child psychiatry could help guide recruitment efforts. Empirical studies have been conducted within the field of internal medicine by Daniels et al to determine factors that affect residents' choices of fellowship [12,13]. Thus far, multiple proposals have been put forth to try to increase recruitment within child psychiatry including shortening the length of training, creating child psychiatry mentorships on the medical student level, and providing clinical experiences in inpatient child psychiatry in medical schools [14][15][16].…”
mentioning
confidence: 99%
“…This was in part due to the forced-choice nature of the method. Some studies reported using Q-methodology as it requires participants to sort cards in relation to each other [ 60 ]. This meant that participants were not able to select the same response for each item, which was reasoned to more accurately portray real-life situations in which decision-making is constrained and must consider multiple factors [ 61 ].…”
Section: Resultsmentioning
confidence: 99%